The magnetic properties and morphology of CoCrPtTa/Cr/AlN thin films - Chang, HS; Shin, KH; Lee, TD; Park, JK (ELSEVIER SCIENCE BV, 1998)
The introduction of AIN and Al underlayers increased the coercivities of CoCrPtTa/Cr films and decreased the coercivity squarenesses. The grains of CoCrPtTa films on Cr/Al and Cr/AlN were more physically isolated than those of CoCrPtTa films on Cr. To examine the effects of underlayers on the magnetic coupling of CoCrPtTa grains, the angular variations of coercivities of magnetic films were measured. The degree of magnetic isolation of CoCrPtTa grains on Cr/Al and Cr/AlN is larger than that of CoCrPtTa grains on Cr. The morphological changes due to the underlayers were closely related to the magnetic coupling, coercivity, and coercivity squareness of magnetic films. (C) 1998 Elsevier Science B.V. All rights reserved.